Development Of Digital Tourism (E-Tourism) In The Governance Of The Hariara Pohan Tourism Village, Samosir District - Dewi Yanti; Budi Prayogi; Ananda Pratiwi; Deby Regina; Putra Adrian; Septi Anggina; Safira Septy Vani (Jurnal Ilmu Sosial Mamangan, 2024)
Hariara Pohan tourist village, digital tourism is one of the potentials that can be utilized to increase tourist attraction and income of village communities and Good governance is needed in managing tourist villages so that digital tourism can provide maximum benefits. This research uses qualitative methods because the researcher wants to know and provide a clear picture of the Development of Digital Tourism (E-Tourism) in the Governance of the Hariarapohan Tourism Village. To make it easier for researchers to collect data, supporting instruments were used, namely interview guidelines, observation guidelines and documentation guidelines. It is hoped that the results of this research will provide insight and understanding regarding the development and management of digital tourism for the community, village officials and Hariara Pohan village tourism managers. By understanding development concepts and effective strategies, you can retain and attract the interest of new customers, and can increase your long-term success as a tourism destination.